Antimicrobial activity, synergism and inhibition of germ tube formation by Crocus sativus-derived compounds against Candida spp. (2nd November 2016) - Carradori, Simone; Chimenti, Paola; Fazzari, Marina; Granese, Arianna; Angiolella, Letizia
Abstract: The limited arsenal of synthetic antifungal agents and the emergence of resistant Candida strains have prompted the researchers towards the investigation of naturally occurring compounds or their semisynthetic derivatives in order to propose new innovative hit compounds or new antifungal combinations endowed with reduced toxicity. We explored the anti- Candida effects, for the first time, of two bioactive compounds from Crocus sativus stigmas, namely crocin 1 and safranal, and some semisynthetic derivatives of safranal obtaining promising biological results in terms of minimum inhibitory concentration/minimum fungicidal concentration (MIC/MFC) values, synergism and reduction in the germ tube formation. Safranal and its thiosemicarbazone derivative5 were shown to display good activity against Candida spp.